End of Sequence Presentation Pattern and Mitigation of Order Effects on Investment Decision-Making - Almilia, Luciana Spica; Hanimah, Khilmiyatul (Jurnal Akuntansi dan Perpajakan, 2024)
Investment is a form of investment activity that develops a business that is expected to provide high returns for the company. This test tests investment decisions based on the belief adjustment model. The research method used in this study is 2x2 which consists of a sequence of evidence (good news followed by bad news or bad news followed by good news) and a series of information (long or short) on the End of Sequence presentation pattern. Participants in this study were students majoring in Accounting at Private University X in Surabaya. The number of participants in this study was 126 participants. The purpose of the study was to test whether there were differences in investment decisions between participants who received good news followed by bad news compared with participants who received bad news followed by good news at the End of the Sequence pattern and long or short series and to examine the effect of the order of evidence (good news followed by bad news or bad news followed by good news) and information series (long or short) on investment decision-making using the End of Sequence presentation pattern. Based on this research, the results obtained are if the information is presented with a Sequence presentation pattern with simple information and a sequence of evidence of good news followed by bad news or bad news followed by good news there is no difference (no order effect) both in the grouping of information series (length or short) and there is no effect of the order of evidence (good news followed by bad news or bad news followed by the good news) in making investment decisions, however, different results are shown by the information series (long or short) where the information series influences investment decision making.